Improving lexical retrieval with LingoTalk: an app-based, self-administered treatment for clients with aphasia - Heide, Judith; Netzebandt, Jonka; Ahrens, Stine; Brüsch, Julia; Saalfrank, Teresa; Schmitz-Antonischki, Dorit (Frontiers in Communication, 2023)
LingoTalk is a German speech-language app designed to enhance lexical retrieval in individuals with aphasia. It incorporates automatic speech recognition (ASR) to provide therapistindependent feedback. The execution and effectiveness of a self-administered intervention with LingoTalk was explored in a case series study.Methods: Three individuals with chronic aphasia participated in a highly individualized, supervised self-administered intervention lasting three weeks. The LingoTalk app closely monitored the frequency, intensity and progress of the intervention. Treatment efficacy was assessed using a multiple baseline design, examining both item-specific treatment effects and generalization to untreated items, an untreated task, and spontaneous speech.Results: All participants successfully completed the intervention with LingoTalk, although one participant was not able to use the ASR feature. None of the participants fully adhered to the treatment protocol. All participants demonstrated significant and sustained improvement in the naming of practiced items, although there was limited evidence of generalization. Additionally, there was a slight reduction in word-finding difficulties during spontaneous speech.Discussion: This small-scale study indicates that self-administered intervention with LingoTalk can improve oral naming of treated items. Thus, it has the potential to complement face-to-face speech-